Kewajaran mahkamah bagi kanak-kanak di Malaysia - Md Isa @ Yusuff, Yusramizza (Universiti Utara Malaysia, 2007)
Court constitutes the main institution that underpins national judicial system for trying and deciding verdict on any criminal and civil cases.There are various types of courts that have been set up according to the types of cases brought before the court including the Court for Children.The Court for Children “bears” the responsibilities for judging and deciding verdict for cases involving children.This court is seen as a sustainable medium for defending the recognized rights of children according to the law and as a platform to rehabilitate child offenders who deviated from the honourable living norms.This article is prepared to discuss the present institution of the Court for Children in Malaysia and the rationale for its establishment.Besides that, this article will cautiously discuss several aspects relating to the Court for Children in Malaysia including its jurisdiction, composition, trial, court proceedings for criminal cases involving children and restriction of the verdict.At the end of this article the author emphasized that the continuity and sustainability of the Court for Children should forever be upheld.